Impact of the COVID-19 pandemic on poisoning induced out of hospital cardiac arrest in South Korea retrospective observational study - Young Taeck Oh; Chiwon Ahn; Yeonkyung Park; Jae Hwan Kim (Scientific Reports)
Abstract Poisoning-induced out-of-hospital cardiac arrest has characteristics distinct from cardiogenic out-of-hospital cardiac arrest, with external factors such as patient intent and environmental influences playing crucial roles. The coronavirus disease 2019 (COVID-19) pandemic has altered societal and healthcare dynamics, potentially influencing poisoning-induced out-of-hospital cardiac arrest outcomes. This study aimed to evaluate the impact of the pandemic on poisoning-induced out-of-hospital cardiac arrest characteristics and survival in South Korea. Participants: Adult patients (aged ≥ 19 years) who experienced poisoning-induced out-of-hospital cardiac arrest before and during the COVID-19 pandemic. This study utilized data from the Out-of-Hospital Cardiac Arrest Surveillance Database from 2016 to 2022. Poisoning-induced out-of-hospital cardiac arrest cases were compared before and during the pandemic by analyzing patient demographics, poisoning agents, prehospital interventions, and outcomes. Multivariate logistic regression identified predictors of survival. During the pandemic, poisoning-induced out-of-hospital cardiac arrest cases involving alcohol, organic solvents, and unspecified drugs increased, while pesticide-related cases declined. Bystander cardiopulmonary resuscitation rates rose, yet survival rates fell (adjusted OR 0.59, CI 0.44–0.80). Prehospital return of spontaneous circulation and witnessed arrests remained the strongest predictors of survival (adjusted OR 13.93 and 4.09, respectively). The COVID-19 pandemic initially impacted poisoning-induced out-of-hospital cardiac arrest outcomes, particularly during its early stages, while later outcomes showed resilience in the emergency medical system. These findings highlight the importance of adaptable public health strategies to address vulnerabilities during large-scale crises.